Influence of Copper Oxide Nanoparticles on Gene Expression of Birch Clones In Vitro under Stress Caused by Phytopathogens - Tatiana A. Grodetskaya; Peter M. Evlakov; Olga A. Fedorova; Vyacheslav I. Mikhin; Olga V. Zakharova; Evgeny A. Kolesnikov; Nadezhda A. Evtushenko; Alexander A. Gusev (Nanomaterials, 2022)
Recently, metal oxide nanoparticles (NPs) have attracted attention as promising components for the protection and stimulation of plant microclones in tissue culture in vitro. However, the effect of NPs on the genetic mechanisms underlying plant adaptive responses remains poorly understood. We studied the effect of column-shaped CuO NPs 50 nm in diameter and 70–100 nm in length at a concentration of 0.1–10 mg/L on the development of phytopathogenic fungi Alternaria alternata, Fusarium oxysporum, and Fusarium avenaceum in culture, as well as on the infection of downy birch micro-clones with phytopathogens and the level of genes expression associated with the formation of plant responses to stress induced by microorganisms. CuO NPs effectively suppressed the development of colonies of phytopathogenic fungi A. alternata and F. avenaceum (up to 68.42% inhibition at 10 mg/L CuO NPs) but not the development of a colony of F. oxysporum. Exposure to the NPs caused multidirectional responses at the level of plant genes transcription: 5 mg/L CuO NPs significantly increased the expression level of the LEA8 and MYB46 genes and decreased the expression of DREB2 and PAL. Infection with A. alternata significantly increased the level of MYB46, LEA8, PAL, PR-1, and PR-10 transcripts in birch micro-clones; however, upon exposure to a medium with NPs and simultaneous exposure to a phytopathogen, the expression of the MYB46, PR-1, and PR-10 genes decreased by 5.4 times, which is associated with a decrease in the pathogenic load caused by the effect of NPs and the simultaneous stimulation of clones in vitro. The results obtained can be used in the development of preparations based on copper oxide NPs for disinfection and stimulation of plant phytoimmunity during clonal micropropagation of tree crops.